A School Literacy Program and Parental Role in Enhancing Students' Literacy - Pambudi, Haryo Aji; Fajrin, Hilma Oktaviana (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
Low reading literacy levels in Indonesian schools are one of the major issues, and the government has urged all schools to start the School Literacy Movement or SLM. As a reference school that successfully implemented this program, State Junior High School 4 Pakem in Yogyakarta, Indonesia, was used in this study to learn how SLM was being implemented there. Additionally, it reveals how parents supported the program. This study is descriptive by using documentation, a questionnaire, and interviews to gather data. This study has revealed the implementation of the School Literacy Program in State Junior High School 4 Pakem, which consists of ten main items. Moreover, the parental role is also crucial for the success of this program. Mostly, the parents hold positive beliefs regarding implementing the school-based literacy program. The parents become role models, communicators, and facilitators during the running program, creating a literacy atmosphere in their family surroundings.